Operative technique of experimental orthotopic liver transplantation in swine - Torres , Orlando Jorge Martins (2005)
Background: Experimental orthotopic liver transplantation is a technically complex procedure requiring a meticulous attention to many details, in order to attain optimal results. Prior to the human liver transplantation, exhaustive training is performed in animal models, in order to attain the demanded expertise in such procedure. Pigs have considerable anatomic similarities to man, as well as comparable physiological and hemodynamic sensitivity, and they have been used as model for experimental researches. Objective: The aim of the present study was to describe the technique of experimental orthotopic liver transplantation in pigs. Methods: Prior to the surgery, animals were kept in a 24 hours fasting, and all operations were carried out under general anesthesia. Female Landrace pigs were divided in two groups: pairs of donor and recipient were used with weights between 32 and 38 Kg. Results: Animals undergone orthotopic liver transplantation and they received whole liver grafts. The surgical procedure was divided in four parts: harvested, back-table, hepatectomy of the recipient and re-implantation. A passive veno-venous by-pass from the left iliac and splenic vein to the left internal jugular vein was performed, in order to avoid severe hemodynamic disturbances during the anhepatic phase. The sequence of the vascular anastomosis was suprahepatic vena cava, portal vein, infrahepatic vena cava, and hepatic artery. Conclusion: The training protocol of experimental liver transplantation in pigs improves the technique and provides an excellent experimental model to the research.